1
$\begingroup$

Please help me. There are equations: $x+y+z=3, x^2+y^2+z^2=5$ and $x^3+y^3+z^3=7$. The question: what is the result of $x^4+y^4+z^4$?

Ive tried to merge the equation and result in desperado. :( Please explain with simple math as I'm only a junior high school student. Thx a lot

$\endgroup$
3
$\begingroup$

solution 2: since $$x^4+y^4+z^4=(x^2+y^2+z^2)^2-2x^2y^2-2y^2z^2-2x^2z^2$$ and $$(xy+yz+xz)^2=x^2y^2+x^2z^2+y^2z^2+2xyz(x+y+z)$$ since $$xy+yz+xz=2,xyz=-\dfrac{2}{3}$$ so $$x^2y^2+y^2z^2+x^2z^2=8$$ so $$x^4+y^4+z^4=5^2-2\cdot 8=9$$

$\endgroup$
  • $\begingroup$ Wow... Such a long solution... I will try... $\endgroup$ – Pebrianto Nov 8 '13 at 11:13
  • $\begingroup$ thanks a lot... Avtually it's not that hard... :D $\endgroup$ – Pebrianto Nov 8 '13 at 17:11
4
$\begingroup$

use this

since $$x^2+y^2+z^2=(x+y+z)^2-2xy-2yz-2xz\Longrightarrow xy+yz+xz=2$$ $$x^3+y^3+z^3-3xyz=(x+y+z)(x^2+y^2+z^2-xy-yz-xz)=(x+y+z)^3-3(xy+yz+xz)(x+y+z)$$ so $$7-3xyz=27-18\Longrightarrow xyz=-\dfrac{2}{3}$$ use $$x^4+y^4+z^4=(x+y+z)(x^3+y^3+z^3)-(xy+yz+xz)(x^2+y^2+z^2)+xyz(x+y+z)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.